Cloning of the trp gene cluster from a tryptophan-hyperproducing strain of Corynebacterium glutamicum: identification of a mutation in the trp leader sequence. - Heery, D M (1993)
Corynebacterium glutamicum ATCC 21850 produces up to 5 g of extracellular L-tryptophan per liter in broth culture and displays resistance to several synthetic analogs of aromatic amino acids. Here we report the cloning of the tryptophan biosynthesis (trp) gene cluster of this strain on a 14.5-kb BamHI fragment. Subcloning and complementation of Escherichia coli trp auxotrophs revealed that as in Brevibacterium lactofermentum, the C. glutamicum trp genes are clustered in an operon in the order trpE, trpD, trpC, trpB, trpA. The cloned fragment also confers increased resistance to the analogs 5-methyltryptophan and 6-fluorotryptophan on E. coli. The sequence of the ATCC 21850 trpE gene revealed no significant changes when compared to the trpE sequence of a wild-type strain reported previously. However, analysis of the promoter-regulatory region revealed a nonsense (TGG-to-TGA) mutation in the third of three tandem Trp codons present within a trp leader gene. Polymerase chain reaction amplification and sequencing of the corresponding region confirmed the absence of this mutation in the wild-type strain. RNA secondary-structure predictions and sequence similarities to the E. coli trp attenuator suggest that this mutation results in a constitutive antitermination response.